Mantra Kidung Rumeksa Ing Wengi - Puspita, Erina; Raehan, Muhammad (Jurnal Ilmiah Wahana Pendidikan, 2024)
Kidung is a poem from Central Javanese literature, which means singing which is thought to protect oneself at night. This research focuses on all the stanzas or poems and discusses one by one in the mantra Kidung Rumeksa Ing Wengi. The method used in this research is descriptive with a qualitative approach.The data obtained was sourced from primary data using skillful free-involved listening techniques and continued with written documentation. The results obtained by Kidung Rumeksa Ing Wengi are used for various purposes, from protection against disease, pests, debt, to obtaining good results in agriculture. Apart from that, this Kidung also contains messages about faith, belief in the role of prophets, friends and angels in protecting and helping humans. In the Kidung Rumeksa Ing Wengi or sometimes also known as the Song of Matra Wedha, there are nine stanzas.. The first to fifth poems are poems that must be read or sung. And the sixth to ninth verses are an explanation of the benefits of the Kidung. Many ordinary people only sing the first to fifth verses.